Pengaruh Konsentrasi Elektrolit Na2SO4 Dalam Produksi Gas Hidrogen Menggunakan Sensor MQ-8 - Dinda Sahara; Rahadian Zainul (Departemen Kimia FMIPA UNP, 2020)
This study aims to analyze the effect of variations Na2SO4 concentration in producing hydrogen gas using the MQ-8 sensor. The method used is electrolysis. The electrolysis process is carried out in a container called a dry cell generator. In this study the Cu and Al electrodes are used as a place for the reduction-oxidation reaction. The use of Cu / Al electrodes in dry cell generators is arranged using layered or sandwich techniques. The use of dry cell generator in the production of hydrogen gas by using the MQ-8 sensor as a measuring tool to calculate the concentration of H2 gas is able to produce a maximum concentration of hydrogen gas of 37 ppm.